Crosstalk Channel Estimation via Standardized Two-Port Measurements. (8th February 2009) - Lindqvist Lindqvist, Fredrik Fredrik; Lindqvist Lindqvist, Neiva Neiva; Dortschy Dortschy, Boris Boris; Ödling Ödling, Per Per; Börjesson Börjesson, Per Ola Per Ola; Ericson Ericson, Klas Klas; Pelaes Pelaes, Evaldo Evaldo
Abstract : The emerging multiuser transmission techniques for enabling higher data rates in the copper-access network relies upon accurate knowledge of the twisted-pair cables. In particular, the square-magnitude of the crosstalk channels between the transmission lines are of interest for crosstalk-mitigation techniques. Acquiring such information normally requires dedicated apparatus since crosstalk-channel measurement is not included in the current digital subscriber line (DSL) standards. We address this problem by presenting a standard-compliant estimator for the square-magnitude of the frequency-dependent crosstalk channels that uses only functionality existing in today's standards. The proposed estimator is evaluated by laboratory experiments with standard-compliant DSL modems and real copper access network cables. The estimation results are compared with both reference measurements and with a widely used crosstalk model. The results indicate that the proposed estimator obtains an estimate of the square-magnitude of the crosstalk channels with a mean deviation from the reference measurement less than 3 dB for most frequencies.